Tinjauan Yuridis Peran Negara dalam Kemitraan antara Penanam Modal Asing sebagai Usaha Besar dengan Usaha Mikro, Kecil, dan Menengah - Rina Taufika Pratidina (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
One of the ways that can be made by Micro, Small and Medium Enterprises in developing their business is through partnerships with Large Enterprises. The partnership pattern is a strategy mandated by the provisions of laws and regulations. In order to ensure that this partnership pattern runs well, the role of the state is important. The problems to be discussed in this paper are related to the role of the host country in foreign investment activities, as well as partnership arrangements between Foreign Investors in their role as Large Enterprises with Micro, Small and Medium Enterprises in Indonesia. This paper is prepared with normative juridical research with an analytical descriptive approach, which aims to describe and analyze systematically, factually, and accurately about the facts, as well as the relationship of the phenomena being investigated. The results of the study conclude that the state plays a role in controlling the flow of foreign investment by applying national provisions that accommodate the interests of foreign investors, but still pay attention to national interests by applying a number of requirements or restrictions on the entry of investment or investment in its territory, for example by applying partnership provisions between Large Enterprises which may take the form of Foreign Investment Companies with Micro, Small and Medium Enterprises.